PENGENALAN PROSES PRODUKSI MIE PADA PESERTA DIDIK SEKOLAH DASAR - Andriani Yasin, Nurfatwa; Masmarulan, Masmarulan; Muliati, Muliati; Artiyany, Megawhati; Afriyani, Afriyani (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2022)
Learning strategies through outing classes to improve aspects of child development. Learning is an important thing that is done in an educational process. Therefore it takes the right learning strategy. As for one of the learning strategies that can be done is through outing class activities. This outing class was conducted by SD Inp students. Toddopuli's flagship by visiting PT. Megah Putra Sejahtera, a company that produces instant noodles under the Megah Mie brand. The purpose of writing this article is to introduce students to the process of mass-producing instant noodles in a machine-run factory. In this community service the lecturer team works closely with the management of PT. Megah Putra Sejahtera, introduced and guided students during the visit. The result of this dedication is that students get additional knowledge and an overview of the world of management, in this case PT. Megah Putra Sejahtera operates and produces instant noodles in bulk packages.